Christian leaders as salt and light in realizing religious moderation in Banyumas Regency - Rahmadi; Muner Daliman; Stevri P.N. Indra Lumintang; Paulus Sentot Purwoko (Technium Social Sciences Journal, 2024)
This study aimed to determine the level of implementation of the salt of the earth and the light of the world, the most dominant dimensions and backgrounds that influence the level of implementation of the salt of the earth and the light of the world based on Matthew 5:13-16, in order to realize religious moderation for the administrators of the Interfaith Harmony Forum (FKUB) and Christian Leaders in Banyumas Regency. From the results of the pre-survey, indications were found that there are still Christian leaders who have not implemented the salt of the earth and the light of the world. This study uses a quantitative method, by measuring Two Dimensions (D) in the concept of implementing the salt of the earth and the light of the world based on Matthew 5:13-16. The results of the study show that first, the level of implementation of the salt of the earth and the light of the world is in the moderate category. Second, the most dominant dimension is becoming the Light of the World (D2). The third dominant background category is the Length of Time as an Administrator / Serving (I10). Therefore, the level of implementation of the salt of the earth and the light of the world among the administrators of the Interfaith Harmony Forum (FKUB) and Christian leaders in order to realize religious moderation in Banyumas Regency needs to be increased, so that in the future it can be higher, and produce better quality of religious moderation for Christians and society in Banyumas Regency.